A holistic approach to thermodynamic analysis of photo-thermo-electrical processes in a photovoltaic cell. (1st September 2016) - Bicer, Yusuf; Dincer, Ibrahim; Zamfirescu, Calin
Graphical abstract: Highlights: A novel approach for energy and exergy analyses of a photovoltaic cell is presented. Photonic, thermal and electrical sub-processes are identified. The irreversibilities caused by the photo-thermo-electrical processes are assessed. Energy and exergy efficiencies are determined for comparison purposes. Abstract: In this study, a novel approach for energy and exergy analyses of a photovoltaic (PV) cell is presented, and the exergy destructions within the relevant optical, thermal and electrical processes are quantified. The present study uses a holistic approach to cover all processes and their interactions inside a PV cell; such as photonic: photons transmission, reflection and spectral absorption, background (blackbody) radiation emission at cell temperature; electrical: electron excitation to create a photocurrent, electron-hole recombination, electrical power transmission to an external load; and thermal: internal heat generation by shunt and series resistances, and heat dissipation by conduction-convection. A physical model which considers the highly complex interaction and interdependence among these processes is introduced based on energy and exergy balances completed by writing various constitutive equations, including correlations for the convective heat transfer coefficient and the photocurrent dependence of the spectral distribution of the quantum efficiency. The irreversibilities caused by the processes are assessed in terms of their relative magnitudes of the exergy destructions. The largest exergy destruction occurs in PV generator-photo current generation process followed by wafer-light absorption process. The overall energy and exergy efficiencies are then determined based on the novel model for seven different atmospheric and ecological conditions. The lowest and highest exergy efficiencies of the PV cell are calculated as 9.3% and 14% for two sample locations as Oshawa in Canada and Emirdag in Turkey, respectively. Furthermore, the effects of varying ambient conditions, light spectrum, wind velocity and solar intensity on the PV cell performance are investigated for comparative evaluations.